LO046: Factors associated with hospital admission following asthma exacerbations: a systematic review. (2nd June 2016) - Rowe, B.H.; Arrotta, N.; Hill, J.; Dennett, E.; Harries, M.
Abstract : Introduction: Patients with asthma frequently present to the emergency department (ED) with exacerbations; however, a select number of patients require admission to hospital. The objective of this study was to summarize the evidence regarding asthma-related hospital admissions and factors associated with these admissions following ED presentation.Methods: Comprehensive literature searches were conducted in seven electronic databases (database inception to 2015); manual and grey literature searches were also performed. Studies reporting disposition for adults after ED presentation were included. Study quality was assessed using the Newcastle-Ottawa Scale (NOS); standardized data-collection forms were used for data extraction. Admission proportions and factors associated with admission at a statistical significance level (p<0.05) were reported.Results: Out of an initial 5865 identified articles, 37 articles met full inclusion criteria. Admission proportions were reported in 25/37 studies, ranged from 1% to 37%, and collectively demonstrated a decline of 9% in admissions between 1993 and 2012. Studies including a >50% Caucasian ethnicity were found to have a median admission proportion of 13% (interquartile range [IQR]= 7, 20) versus studies with >50% non-Caucasian ethnicity at 22% (IQR=20, 28). Age, female sex, and previous hospitalizations for asthma exacerbation were the most individually identifiable factors associated with admission. Presenting features and medication profile were the most frequent domains associated with admission.Conclusion: Admission rates have decreased approximately 9% in a nearly 20-year span and seem to be higher in studies involving mostly non-Caucasian ethnic groups. Demographic factors, markers of severity obtained by history or at ED presentation, and medication profile could be assessed by ED clinicians to effectively discern patients at high risk for admission.